1988
DOI: 10.1002/cm.970090307
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule rearrangements during mitosis in multinucleate cells

Abstract: The peroxidase-antiperoxidase (PAP) method for the detection of polymerized tubulin has been used to study the microtubule rearrangements during mitosis in PtK1 and HeLa multinucleate cells obtained by polyethyleneglycol (PEG)-mediated fusion. We demonstrate here that the transition of the microtubular cytoskeleton from interphase to mitosis is an inducible event and independent of the factor(s) responsible for chromatin condensation and nuclear envelope breakdown. However, for the induction of the microtubule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…It, therefore, remains to be determined whether separating centrosomes interact to form a spindle-shaped array of Mts in the absence of chromosomes, and if so whether this structure is stable. In this regard, homokaryons and heterokaryons, formed by fusing the same or different cell types, sometimes enter mitosis with one or more centrosomes that are too far removed from the chromosomes to form an association [e.g., Peterson and Berns, 1979;Armas-Portela et al, 1988]. We reasoned that this system could be used to determine the extent to which free centrosomes interact in the absence of associated chromosomes during mitosis in mammalian cells.…”
Section: Introductionmentioning
confidence: 99%
“…It, therefore, remains to be determined whether separating centrosomes interact to form a spindle-shaped array of Mts in the absence of chromosomes, and if so whether this structure is stable. In this regard, homokaryons and heterokaryons, formed by fusing the same or different cell types, sometimes enter mitosis with one or more centrosomes that are too far removed from the chromosomes to form an association [e.g., Peterson and Berns, 1979;Armas-Portela et al, 1988]. We reasoned that this system could be used to determine the extent to which free centrosomes interact in the absence of associated chromosomes during mitosis in mammalian cells.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps the phosphorylation of the 220K protein may play a role in this process, as it has been reported that phosphorylation of MAP-IB polypeptides may favour their association with microtubules (Dfaz-Nido et al 1988). Furthermore, it has been observed that centrosomes are able to organize the mitotic spindle only after nuclear envelope breakdown (Armas-Portela et al 1988;Vandre et al 1984a,6). This transformation has-been partly ascribed to the binding of nuclear phosphoproteins (Vandre et al 1984a,b).…”
Section: \ -220mentioning
confidence: 99%